(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Radon in borehole water serves as a source of natural radioactivity exposure through indoor air. Determination of naturally occurring radionuclides concentration in ground and surface waters is useful as a contribution to environmental health studies. In this research, statistical analysis of radon concentration in (borehole) water was conducted in Katsina state. The aim of this study is to analyse statistically the concentration of radon in borehole water in Katsina state and to establish a possible relationship between radon activity concentration in borehole water and underlying rock types. A total of 110 water samples were collected and analysed using Tri-carb 1000 Liquid Scintillation Counter (LSC) at the Centre for Energy Research and Training, Ahmadu Bello University. The overall average concentration of 222Rn was found to be 69 ± 3 Bql-1 with geological formations, G8 and G7 having the highest and lowest concentrations with values of 75 ± 10 Bql-1 and 57 ± 4 Bql-1 respectively, which are higher than the world average values of 10 Bql-1 set by WHO and 11.1 Bql-1 set by USEPA. The results showed that radon concentrations are clearly correlated to rock types with acidic intrusive rocks associated with values which sedimentary rocks are associated with lower concentrations.